Unemployment and Social Integration: Analysing the Impact of Financial Strain, Social Roles, and Identity - Carlotta Giustozzi (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Relations to family and friends are a~key dimension of an individual's social integration and, by extension, are crucial for the social cohesion of societies. Based on that principle, this study explores the effects of unemployment on close personal relations and asks whether negative effects of unemployment are primarily explicable as financial losses or social aspects of identity. This analytical approach goes beyond analysing the direct effects of unemployment through differentiating effects by gender, household composition, and individual work and family values. In doing so, it examines the channels through which unemployment has the potential to erode social relations. Individual fixed effects models based on German Socio-Economic Panel (SOEP) data from 1990 to 2017 reveal that financial strain fails to explain the effects of unemployment on social relations. However, the results suggest that social identity is influential in shaping unemployment effects. Although men see a~reduction in their personal relations when experiencing unemployment, women's unemployment experiences do not affect the frequency of their social interactions. Moreover, the fact that unemployment leads to a~reduction of men's social contacts, particularly among those living with children, points to potential difficulties in performing the social role of the family provider. Finally, placing high importance on having children, partnership and caring for others mitigates negative unemployment effects for men. – – Nahe soziale Beziehungen stellen eine wichtige Dimension sozialer Integration dar und beeinflussen dadurch den sozialen Zusammenhalt auf gesellschaftlicher Ebene. Vor diesem Hintergrund untersucht die vorliegende Studie den Einfluss von wiederholten und längeren Arbeitslosigkeitserfahrungen auf Freundschafts- und Familienbeziehungen und analysiert, inwieweit negative Effekte auf finanzielle Schwierigkeiten oder auf Identitäts- und Rollenkonflikte zurückzuführen sind. Dabei werden nicht nur direkte Effekte von Arbeitslosigkeit betrachtet, sondern es wird nach Geschlecht, Haushaltszusammensetzung sowie individuellen Werten in Bezug auf Arbeit und Familie differenziert, um so die Mechanismen zu ergründen, die eine Erosion dieser sozialen Bindungen erklären können. Auf Daten des Sozio-oekonomischen Panels (SOEP) für den Zeitraum von 1990 bis 2017 basierende "fixed effects"-Modelle zeigen, dass weder die objektive noch die subjektive Verschlechterung der finanziellen Lage von Haushalten erklären kann, warum sich Arbeitslosigkeitserfahrungen negativ auf nahe soziale Beziehungen auswirken. Die empirischen Ergebnisse legen jedoch nahe, dass die soziale Identität ausschlaggebend ist. Auffällig ist, dass nur Männer weniger häufig mit Freunden und Familie interagieren, wenn sie von Arbeitslosigkeit betroffen sind. Dies zeigt sich besonders, wenn sie mit Kindern in einem Haushalt wohnen, was auf Schwierigkeiten deutet, die Rolle des Familienernährers auszufüllen. Schließlich zeigt sich, dass familienbezogene Werteinstellungen den negativen Effekt von Arbeitslosigkeit auf nahe soziale Beziehungen abmildern.
Keywords: 300; Personal relations; Gender; Household composition; Work values; Family values; Nahe soziale Beziehungen; Soziale Identität; Einstellungen zu Arbeit; Familienbezogene Einstellungen; Geschlechterrollen